Kindler syndrome - Angelova, Irena (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Kindler syndrome is a rare hereditary disorder characterized by acral blister formation in infancy and childhood, progressive poikiloderma, cutaneous atrophy and increased photosensitivity. Since itwas first described in 1954, less than 100 cases have been reported worldwide. Recently it has been reported that Kindler syndrome is the first genodermatosis caused by a defect in the actin-extracellular matrix linkage, and the gene was mapped to chromosome 20p12.3. The clinical features of the syndrome have been annotated by different authors but the definite of criteria to confirm the diagnosis have not yet been generally accepted. We report a case of Kindler syndrome that presents a full spectrum of clinical manifestations, and we propose a setof clinical criteria for diagnosis.
Keywords: dermatologija; fotosenzibilnost; Fotosenzibilnost, motnje; genetske bolezni; Middle Age; Photosensitivity Disorders; Poikiloderma Congenitale; Poikilodermija prirojena; Srednja leta